Hadronic energy resolution of a combined high granularity scintillator calorimeter system - Repond, Jose O.; Kaplan, Alexander; Schultz-Coulon, Hans-Christian (Journal of Instrumentation, 2018)
This paper presents results obtained with the combined CALICE Scintillator Electromagnetic Calorimeter, Analogue Hadronic Calorimeter and Tail Catcher & Muon Tracker, three high granularity scintillator-silicon photomultiplier calorimeter prototypes. The response of the system to pions with momenta between 4 GeV/c and 32 GeV/c is analysed, including the average energy response, resolution, and longitudinal shower profiles. Two techniques are applied to reconstruct the initial particle energy from the measured energy depositions; a standard energy reconstruction which is linear in the measured depositions and a software compensation technique based on reweighting individually measured depositions according to their hit energy. The results are compared to predictions of the GEANT 4 physics lists QGSP_BERT_HP and FTFP_BERT_HP.
Gesehen am 04.02.2020